1973
DOI: 10.1126/science.182.4111.492
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Identification of a Visual Area in Shark Telencephalon

Abstract: Optic nerve stimulation in the shark evokes short-latency telencephalic field potentials localized to the ipsilateral, posterior central nucleus. Such a well-defined visual area in elasmobranch telencephalon further challenges classical formulations of forebrain evolution. Moreover, its ipsilateral representation confirms recent evidence for a crossed thalamotelencephalic visual projection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(20 citation statements)
references
References 7 publications
2
18
0
Order By: Relevance
“…These projections were considered to be homologous to the ascending thalamocortical projections found in 'higher' vertebrates [Ebbesson and Schroeder, 1971;Ebbesson, 1980]. Subsequently, a number of anatomical and physiological studies confirmed the presence of ascending projections to the pallium [Cohen et al, 1973;Platt et al, 1974;Bullock and Corwin, 1979;Luiten, 1981b;Bodznick and Northcutt, 1984;Bleckmann et al, 1987Bleckmann et al, , 1989Smeets and Northcutt, 1987;Fiebig and Bleckmann, 1989;Bodznick, 1991]. The conclusion at that time, which is still believed today, is that the telencephalon of elasmobranchs has large 'non-olfactory' areas that are innervated by ascending diencephalic projections carrying information from other sensory modalities to the telencephalon.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…These projections were considered to be homologous to the ascending thalamocortical projections found in 'higher' vertebrates [Ebbesson and Schroeder, 1971;Ebbesson, 1980]. Subsequently, a number of anatomical and physiological studies confirmed the presence of ascending projections to the pallium [Cohen et al, 1973;Platt et al, 1974;Bullock and Corwin, 1979;Luiten, 1981b;Bodznick and Northcutt, 1984;Bleckmann et al, 1987Bleckmann et al, , 1989Smeets and Northcutt, 1987;Fiebig and Bleckmann, 1989;Bodznick, 1991]. The conclusion at that time, which is still believed today, is that the telencephalon of elasmobranchs has large 'non-olfactory' areas that are innervated by ascending diencephalic projections carrying information from other sensory modalities to the telencephalon.…”
mentioning
confidence: 81%
“…At that time, only the secondary and tertiary olfactory projections were known, and these do not reach the dorsomedial pallium [Ebbesson and Heimer, 1970;Ebbesson, 1972;Smeets, 1983;Dreyer and Graziadei, 1994]. Then, ascending non-olfactory projections to the dorsomedial pallium were discovered, which led to the valid conclusion that other sensory modalities occupy these non-olfactory areas [Cohen et al, 1973;Platt et al, 1974;Bullock and Corwin, 1979;Luiten, 1981b;Bodznick and Northcutt, 1984;Bleckmann et al, 1987Bleckmann et al, , 1989Smeets and Northcutt, 1987;Fiebig and Bleckmann, 1989;Bodznick, 1991]. The problem was that these studies focused on non-olfactory sensory systems and nobody investigated further olfactory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Karamian et al (1973) have given evidence that dorsal column stimulation of the spinal cord in the lamprey (Lampetra fluviatilis) causes telencephalic evoked potentials, so somatic sensory information may project to this area. Cohen et al (1973) have also claimed the existence of a visual projection, in the telencephalon of the shark (Ginglymostoma cirratum), in the central telencephalic area. Platt et al (1974) have reported that various types of input in some elasmobranchs, primarily Torpedo and Scyliorhinus, can cause specific evoked potentials in the telencephalon.…”
Section: Specific Sensory Afferencementioning
confidence: 96%
“…A relatively enlarged telencephalon, as reported in members of Carcharhinidae and Sphyrnidae , has been associated with species that live in complex habitats and the social interactions that occur in those habitats [Striedter, 2005], similarly documented in other vertebrate groups [Riddell and Corl, 1977;Huber et al, 1997;Pollen et al, 2007;Shumway, 2008]. In particular, development of the central nucleus has been linked to complex social behaviors such as dominance hierarchies and other forms of 'social intelligence' [Cohen et al, 1973;Graeber, 1978;Graeber et al, 1978;Demski and Northcutt, 1996]. An enlarged central nucleus of the dorsal pallium has been recorded in Cetorhinus maximus [Kruska, 1988], although was described as being less developed than that of R. typus [Sato, 1986].…”
Section: General Brain Organizationmentioning
confidence: 99%